The Effect of Herbal Steam Bath to Increasing Breast Milk Production in Postpartum Mothers - Shinta Wurdiana Rhomadona; Dianita Primihastuti (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
The importance of breastfeeding has strong evidence[1]. But in reality, there are many obstacles in its implementation[2]. Data shows that exclusive breastfeeding in Indonesia is 89.4% (2020). Physical factors due to complications or fatigue after giving birth also have an impact on breast milk production, so mothers tend to fail to exclusively breastfeed[3][1]. A non-pharmacological method that can reduce postpartum stress, increase comfort and body fitness so as to help stimulate breast milk production is the herbal steam bath.[4]. This is a culture of local wisdom that is still preserved in various parts of Indonesia as a therapy for postpartum mothers. The purpose of this study was to analyze the effect of herbal steam bath on breast milk production for postpartum mothers in Surabaya. The design of this study was a quasi-experimental (two group pre-post test design). This research was conducted on postpartum mothers in Surabaya. The study was conducted for 6 months. Determination of the sample using purposive sampling technique. The treatment group was given intervention for 1 week as much as 2x, namely Herbal Steam Bath for 5-20 minutes. Endorphin massage was performed in the control group for 1 week with a frequency of 2 times/week for 20 minutes. Each group was given a pre-test and post-test to determine the production of breast milk with indicators of increased baby weight, increased frequency of urination and defecation. Data analysis with independent T-test and Mann Whitney. The results showed that there was a significant effect of herbal steam baths on increasing breast milk production with a value of = 0.012 or <0.05. There was a significant difference in milk production in the treatment group compared to the control group with a value of = 0.004 or <0.05. Conclusion: By doing of herbal steam baths it can increase milk production.